2006
DOI: 10.1017/s0317167100004996
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam as Add-on Therapy in Children with Epileptic Encephalopathy

Abstract: ABSTRACT:Rationale:Clobazam has been used successfully in adults and children with partial epilepsy. The purpose of this study was to evaluate the safety and efficacy of clobazam as add-on therapy in children with epileptic encephalopathy.Methods:This was a retrospective study conducted at the pediatric epilepsy clinic of our university hospital. Children less than 18-years of age with epileptic encephalopathy were included in the study. Clobazam was introduced as add-on therapy, starting with 5 mg/Kg/day and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…Many studies have demonstrated that when a response to clobazam is present, the majority of patients experience significant (i.e., >90%) reduction in seizure frequency. 2,7,11 We found that 60% to 84% of responders reported reduction in seizure frequency >90%. In our cohort of medically intractable patients, such a remarkable reduction in seizure frequency is impressive.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Many studies have demonstrated that when a response to clobazam is present, the majority of patients experience significant (i.e., >90%) reduction in seizure frequency. 2,7,11 We found that 60% to 84% of responders reported reduction in seizure frequency >90%. In our cohort of medically intractable patients, such a remarkable reduction in seizure frequency is impressive.…”
Section: Discussionmentioning
confidence: 75%
“…Seizure freedom on clobazam therapy has been reported in 12% to 26% of patients with localization-related epilepsy and 9% to 40% of patients with generalized epilepsy, similar to our seizure-free rate of 11%. [6][7][8][11][12][13] Age at epilepsy onset, epilepsy duration, patient age, gender, and etiology of epilepsy had no impact on outcome. These are important findings, given clobazam is approved in the United States to treat seizures associated with Lennox-Gastaut syndrome in children aged >2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two retrospective studies on the efficacy of clobazam as addon therapy for pediatric patients also reported significant reductions in seizure frequency84,85 (Table 1). Da Silveira et al84 evaluated 100 patients who received clobazam as addon therapy for refractory focal epilepsy, and 33% of these patients had a 75% or greater decrease in seizure frequency.…”
Section: Clinical Trials In Lennox–gastaut Syndrome and Other Pediatrmentioning
confidence: 98%
“…Da Silveira et al84 evaluated 100 patients who received clobazam as addon therapy for refractory focal epilepsy, and 33% of these patients had a 75% or greater decrease in seizure frequency. Silva et al85 reviewed the efficacy of clobazam as addon therapy for 97 pediatric patients with epileptic encephalopathies. Of the patients in this study, 28 had LGS.…”
Section: Clinical Trials In Lennox–gastaut Syndrome and Other Pediatrmentioning
confidence: 99%